A review of predictive control techniques for matrix converters: part II - Rivera, Marco; Wheeler, Patrick; Olloqui, A.; Khaburi, D.A. (2016)
The second part of this paper presents an overview of different control strategies and applications for matrix converters (MCs) where predictive control techniques are applied. It will be shown that predictive control is a promising alternative to control MCs due to its simplicity and flexibility to include different constrains in the con¬trol for different industrial applications such as renewable energies, grid interconnection, multi-drives systems control, among others. In addition, some limitations and weaknesses of predictive control in MCs such as variable switching frequency, high dependence on the predictive model quality and high computational cost, will be discussed as well as some future trends in control strategies and its application to other topologies or loads.